Intraoperative Anesthesiology Management and Patient Outcomes for Surgical Revascularization for Moyamoya Disease: A Review and Clinical Experience - Williams, George W., II; Jones, William S.; Chaudhry, Rabail; Cai, Chunyan; Pednekar, Greesha S.; Long, Alia C.; Chouhan, Shilpa; Artime, Carlos; Wegner, Robert C.; Grewal, Navneet K.; Patterson, Velvet M.; Contreras, Daniel A.; Ferrario, Lara (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Moyamoya disease (MMD) is a rare cerebrovascular condition, often presenting as a headache or stroke in adults. Anesthetic management of this illness may challenge providers because it can affect the long-term neurologic outcome and hospital length of stay (LOS) in patients with MMD.Materials and Methods A literature search was conducted to assess etiology and epidemiology, as well as existing reports of intraoperative management of MMD. Due to sparse findings, the search was expanded to include studies of the use of intraoperative anesthetic agents during other neurosurgical procedures. We also retrospectively reviewed all MMD cases from January 1, 2009, to December 31, 2015, at Memorial Hermann Hospital-Texas Medical Center, where intraoperative management involved craniotomy and surgical revascularization. Data were collected primarily on the use of several anesthetic agents. The LOS and any adverse events were also recorded for each case. The data were divided into two equivalent case cohorts: (1) January 1, 2009, to February 18, 2013, and (2) February 19, 2013, to December 31, 2015.Results Remifentanil use notably increased between the first and second time periods while fentanyl use decreased. Desflurane usage also demonstrated an observed increase when our two cohorts were compared. Additionally, there was a decrease in the mean LOS between the first and second periods of 3.9 and 3.3 days, respectively.Conclusion Increasing use of remifentanil in MMD cases could be attributed to its ability to provide more stable hemodynamics during induction, maintenance, and emergence of anesthesia when compared with fentanyl. Lower systolic pressures, diastolic pressures, and heart rates were reported in patients receiving remifentanil over fentanyl.
Keywords: moyamoya; neurosurgery; balanced anesthesia; revascularization